Tác động phi tuyến của giá dầu đến tăng trưởng, lạm phát, thất nghiệp và thâm hụt ngân sách - Nguyen Thi Ngoc , Trang; Dinh Thi Thu , Hong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
In oil-exporting countries such as members of the OPEC, fluctuations in oil prices exert a significant impact on the economy. Currently, a sharp reduction in oil prices results in several adverse effects; however, for such a crude-oil exporter that is also an importer of petroleum products as Vietnam, does a rise or drop in oil prices is beneficial to its economic development? This paper attempts to determine the oil price threshold while analyzing its effects on macro factors, such as inflation, economic growth, budget deficits, and unemployment over the 2000–2015 period. Using TVAR model, we detect the oil price threshold of USD26.7/barrel. Moreover, an increase in the oil price, which exceeds this threshold, will cause a rise in inflation rates, budget deficits, and degree of unemployment. Nevertheless, there is no statistical evidence of the impact of oil prices on GDP growth.